Late Jurassic-Early Cretaceous stress accumulation for Phase B of the Yanshanian Orogeny in the northern North China Craton. (1st July 2023) - Hou, Yifei; Zhao, Pan; Hao, Wenxing; Zhang, Min; Jia, Zhenhua; Qin, Huafeng; Deng, Chenglong; Zhu, Rixiang
Graphical abstract: Highlights: A compressional stress state was identified for the Late Jurassic–Early Cretaceous terrestrial red beds in the North China Craton. The North China Craton was under stress accumulation stage during the Late Jurassic-Early Cretaceous. Regional compression resulted from the Mongol-Okhotsk ocean closure and Paleo-Pacific plate subduction. Abstract: The Yanshanian Orogeny was the most prominent tectonic event in the North China Craton during the Jurassic-Cretaceous, which involved episodic compression and extension. The Early Cretaceous Phase B of the Yanshanian Orogeny is one of the most intense shortening events of this orogenesis, represented by regional angular uncomformity above the Tuchengzi Formation. However, mechanism of tectonic regime transition from pre-Phase B extension to Phase B compression is still controversial. The Tuchengzi Formation below the angular uncomformity may record this tectonic transition, which will be a potential target to decipher this problem. Therefore, we performed anisotropy of magnetic susceptibility (AMS) and U-Pb geochronological studies on the Tuchengzi Formation. The results show that during its deposition (153–141 Ma), the Yanshan fold and thrust belt was under N-S compression in the western and middle segments, whereas NW-SE compression in the eastern part. By compilation of geological evidence, we proposed that between the Tiaojishan Formation-represented regional extension (165–153 Ma) and Phase B of the Yanshanian Orogeny (141–138 Ma), there was a stage of stress concentration. Besides, the ∼12 myr accumulation of compressional stress finally resulted in the Phase B deformation and sedimentary hiatus. From integrated analyses of evidence from AMS, magmatism, fold-and-thrust systems, we suggested that during Phase B of the Yanshanian Orogeny, the western and central parts of the Yanshan fold and thrust belt was influenced mainly by closure of the Mongol-Okhotsk Ocean, whereas the eastern part was affected mainly by subduction of the Paleo-Pacific oceanic plate.